Bridging the Gap: Quality by Design as a Catalyst for Enhanced Quality Management Systems in Biopharmaceutical Manufacturing - Saxena, Shivang; Saxena, Shubhi; Diksha; Patil, Niraj S.; Ranjan, Animesh; Singh, Amandeep (Current Drug Discovery Technologies, 2025)
The document emphasizes the importance of addressing key issues in Quality Management Systems (QMS) to stay competitive and provide high-quality goods and services in a dynamic market. It highlights the need to adopt novel quality management techniques for long-term success. The fundamentals of Quality by Design (QbD) are discussed, tracing back to pioneers like Joseph M. Juran and the Six Sigma concept for effective implementation. QbD is described as a systematic approach focusing on risk management, Quality Target Product Profile (QTPP), and Critical Quality Attributes (CQAs) to create products meeting predetermined quality standards. QbD incorporates quality concepts into the development and production processes. Its goal is to guarantee the quality of the product by determining and managing important factors. Manufacturers can be flexible with it while still adhering to strict quality standards. It signifies a change in the industry's paradigm.
Keywords: regulatory framework